Evaluation of the use of subcutaneous drains to prevent wound complications in abdominal surgeries - Manoharan, G. V.; Sivakumar, T.; Kumar, M. Ashok (International Surgery Journal, 2018)
Background: Wound complications like surgical site infections (SSI) and wound dehiscence are common following abdominal surgery for peritonitis. Drains have been used to remove collections from the early days of surgery. The use of drains to remove subcutaneous collections to prevent wound complications needs to be studied. Methods: Sixty patients who underwent surgery for peritonitis were selected for the study. 30 patients underwent conventional abdominal wall closure while the other 30 had suction drains inserted in the subcutaneous tissue. Wounds were observed for complications and time for healing. Results: The incidence of SSI was significantly less in Group A (23%) than in Group B (60%). Similarly, wound dehiscence occurred in 43% of SSI cases in Group A as against 89% of SSI cases in Group B, the difference of which was statistically significant. The mean duration of hospital stay was significantly less when subcutaneous suction drain was placed (9 days). Conclusions: Subcutaneous suction drainage tube is an effective method of abdominal wall closure in cases of peritonitis when compared to conventional primary skin closure as it significantly reduces the incidence of SSI, wound dehiscence, wound secondary suturing and duration of hospital stay.